A New Nanocomposite for Inducing Demineralized Dentin Remineralization - Ban G; Long J; Yan K; Li Q; Huang X; Wei X; Xie F (International Journal of Nanomedicine)
Guifei Ban,1,2,* Jindong Long,1,2,* Kaiqi Yan,1,2,* Qiurong Li,1,2 Xiaoman Huang,1,2 Xiaolang Wei,1,2 Fangfang Xie1,2 1College & Hospital of Stomatology, Guangxi Medical University, Nanning, Guangxi, 530021, People’s Republic of China; 2Guangxi Key Laboratory of Oral and Maxillofacial Rehabilitation and Reconstruction, College of Stomatology, Hospital of Stomatology, Guangxi Medical University, Nanning, Guangxi, China; Guangxi Health Commission Key Laboratory of Prevention and Treatment for Oral Infectious Diseases, College of Stomatology, Hospital of Stomatology, Guangxi Medical University, Nanning, Guangxi, 530021, People’s Republic of China*These authors contributed equally to this workCorrespondence: Fangfang Xie, Email xiedualfang@163.comObjective: This study aimed to investigate a method for promoting the remineralization of demineralized dentin collagen fibers, with the objective of enhancing the bonding strength and durability of dentin resin while reducing the incidence of secondary caries.Methods: A mineralized solution, PAMAM-COOH/ACMP-MDP ethanol solution, was prepared, consisting of the dendritic organic macromolecule PAMAM-COOH, magnesium ions, and methacryloyloxydecyl dihydrogen phosphate (MDP). We examined its storage stability. The solution underwent comprehensive characterization using various techniques, including Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD), Transmission Electron Microscopy (TEM), STEM-EDX mapping, and Selected Area Electron Diffraction (SAED). Additionally, remineralization of demineralized dentin was induced by both control groups and the PAMAM-COOH/ACMP-MDP group. The effects were observed using a laser scanning confocal fluorescence microscope (CLSM), scanning electron microscopy (SEM), and TEM.Results: The PAMAM-COOH/ACMP-MDP ethanol solution we prepared maintained stable physicochemical properties after two months of storage. It exhibited good dispersibility, retained an amorphous phase, and maintained a nanometer size with excellent stability. The results from CLSM indicated that, compared to the control group, the PAMAM-COOH/ACMP-MDP ethanol solution could induce partial remineralization of demineralized dentin in deeper dentin tubules. The SEM results indicated that the PAMAM-COOH/ACMP-MDP group exhibited distinct characteristics of collagen fiber remineralization, both on the surface and within the deep dentin tubules. The collagen fibers in this group were thicker and more mineralized. Furthermore, significant remineralization features of collagen fibers were observed in the peritubular dentin of the PAMAM-COOH/ACMP-MDP group as evidenced by TEM.Conclusion: The PAMAM-COOH/ACMP-MDP ethanol solution exhibits thermodynamic stability, uniform dispersion, and the capability to induce remineralization of demineralized dentin collagen fibers. These findings highlight the potential of dendritic macromolecules for the biomimetic mineralization of dentin collagen and underscore the feasibility of utilizing ethanol-based primers in the development of new adhesives and their clinical applications.Keywords: nanocomposite, dentin remineralization, polyamidoamine, collagen